Datasheet-Based Efficiency Comparison Analysis of Alternating Current (AC) And Direct Current (DC) Electrical Systems - Halim, Levin; Cevin Hutabarat, Frans; Sucianti Adam, Alma; Icha Pratama Manafe, Lucky (Riviera Publishing, 2023)
In today's electrical infrastructure, a significant portion continues to depend on the AC (alternating current) system, necessitating energy conversion from DC (direct current) to AC during power generation and vice versa when reaching consumers. Nonetheless, as renewable energy sources and DC-based electronic devices gain popularity, the DC electrical system presents an attractive alternative. This research compares the energy efficiency between AC and DC electrical systems in school buildings. Through literature review and energy analysis in school buildings, the study found that the DC electrical system is significantly more efficient, achieving an efficiency rate of 89%. In contrast, the AC system only reaches 84%. The implications of this research provide valuable insights for implementing more efficient and sustainable electrical systems in buildings in the future.